2009
DOI: 10.1111/j.1939-1676.2008.0254.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Transfusion Reactions and Retention of Procoagulant and Anticoagulant Factor Activities in Equine Plasma

Abstract: Background: The extent of preservation of clotting factors and incidence of transfusion reactions to noncommercial equine plasma is not documented.Hypothesis: Equine frozen plasma would retain its coagulation factor activity within the reference range and the incidence of transfusion reactions would be low.Animals: Ten plasma donor horses. Fifty clinically ill hospitalized horses receiving plasma were reviewed to determine the incidence of reactions.Methods: In vitro study and retrospective case review. Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
2
13
3
1
Order By: Relevance
“…Clotting factor activities in horses in the current study differed slightly from those reported previously . These differences may relate to the numbers of animals used, to inter‐laboratory differences or to breed differences .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Clotting factor activities in horses in the current study differed slightly from those reported previously . These differences may relate to the numbers of animals used, to inter‐laboratory differences or to breed differences .…”
Section: Discussioncontrasting
confidence: 76%
“…No differences were found between species for Factors V and VIII. Activity of Factor XI was more than twice as high in donkeys as in horses and its concentrations were markedly outwith the ranges reported in a previous study conducted in horses (Supplementary Item ). The other factors in the contact system pathway showed heterogeneous results.…”
Section: Resultssupporting
confidence: 58%
“…; Wilson et al . ). The lifespan of transfused autologous erythrocytes is significantly longer than their allogenic counterparts, although lifespan is influenced by storage duration.…”
Section: Discussionmentioning
confidence: 97%
“…Advantages include a longer lifespan of the transfused erythrocytes and minimised risk of transfusion reactions (Mudge et al 2004). Transfusion reactions can be immunemediated or nonimmune-mediated, immediate or delayed and are more common with whole blood (16%, Hurcombe et al 2007) compared to plasma (0-10%, Hardefeldt et al 2009;Wilson et al 2009). The lifespan of transfused autologous erythrocytes is significantly longer than their allogenic counterparts, although lifespan is influenced by storage duration.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion of whole blood or blood products is a commonly performed procedure in the hospitalised horse, Auto-transfusion in a case of haemoabdomen either for treatment of haemorrhage or anaemia, using whole blood or packed red blood cells (RBC) or as a supportive measure for systemically ill horses suffering from a range of disorders such as hypoalbuminaemia, systemic inflammation, sepsis, disseminated intravascular coagulation or immune mediated thrombocytopaenia using fresh, frozen or platelet-rich plasma. Transfusion reactions are a recognised complication of administration of blood products in the horse and have been reported more commonly with administration of whole blood (16%, Hurcombe et al 2007) compared to plasma (0-10%, Hardefeldt et al 2009;Wilson et al 2009). Frequently, blood typing and cross-matching are not performed prior to the first administration of whole blood, due to the relatively low risk of a reaction if no previous transfusions have been administered and the impracticality of performing a cross-match in an emergency situation.…”
Section: Discussionmentioning
confidence: 99%